Electrochemical synthesis of FeNx doped carbon quantum dots for sensitive detection of Cu2+ ion - Siyuan Sun; Weijie Bao; Fan Yang; Xingru Yan; Yang Sun; Ge Zhang; Wang Yang; Yongfeng Li (Green Energy & Environment, 2023)
A novel strategy was developed to fabricate FeNx-doped carbon quantum dots (Fe-N-CQDs) to detect Cu2+ ions selectively as a fluorescence probe. The Fe-N-CQDs were synthesized by an efficient electrolysis of a carbon cloth electrode, which was coated with monoatomic iron-anchored nitrogen-doped carbon (Fe-N-C). The obtained Fe-N-CQDs emitted blue fluorescence and possessed a quantum yield (QY) of 7.5%. An extremely wide linear relationship between the Cu2+ concentration and the fluorescence intensity was obtained in the range from 100 nmol L−1 to 1000 nmol L−1 (R2 = 0.997), and the detection limit was calculated as 59 nmol L−1. Moreover, the Fe-N-CQDs demonstrated wide range pH compatibility between 2 and 13 due to the coordination between pyridine nitrogen and Fe3+, which dramatically reduced the affection of the protonation and deprotonation process between H+ and Fe-N-CQDs. It is notable that the Fe-N-CQDs exhibited a rapid response in Cu2+ detection, where stable quenching can be completed in 7 s. The mechanism of excellent selective detection of Cu2+ was revealed by energy level simulation that the LUMO level of Fe-N-CQDs (−4.37 eV) was close to the redox potential of Cu2+, thus facilitating the electron transport from Fe-N-CQDs to Cu2+.